The Application of Indirect Evidence in Cartel Practices - Novriani, Dasjagarni Ulinai; Suyanto, Heru (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2024)
KPPU tasked with overseeing business competition, confronts challenges in identifying and proving cartel practices. According to Article 1, paragraph 7 of Law Number 5 of 1999, agreements among business actors need not be written to constitute cartels, potentially allowing for covert operations. This absence of written documentation complicates KPPU's efforts to substantiate suspicions of cartel behavior, often hindering the discovery of tangible evidence necessary for legal proceedings. Consequently, proving cartel activities in court becomes arduous, as direct evidence is typically required while these agreements may lack physical documentation, posing ongoing challenges for regulatory enforcement. This research uses normative juridical research method. The aim of this research is to understand how indirect evidence is applied in the cooking oil cartel practices and reviewing the forms of legal protection for consumers who are harmed.